Sequential base-promoted formal (4+2) allenoate based cycloaddition: synthesis of functionalized acridines - Shirazian, Toktam S.; Tejeneki, Hossein Zahedian; Nikbakht, Ali; Rominger, Frank; Balalaie, Saeed (European journal of organic chemistry, 2022)
Base-promoted formal [4+2] cycloaddition reaction of (Z)-2-(2-hydroxy-2-alkylvinyl)quinoline-3-carbaldehydes and allenoates represents an efficient method for the synthesis of functionalized acridines through a sequential Michael addition, aldol condensation, and isomerization process in a mild condition. This new approach tolerates a wide range of (Z)-2-(2-hydroxy-2-alkylvinyl)quinoline-3-carbaldehydes and allenoates and affords the functionalized acridines in good to excellent yields. The exclusive selectivity, high atom economy, and high bond-formation efficiency of this method makes it a valuable approach for the synthesis of acridine backbones.